2022
DOI: 10.3389/fimmu.2022.877634
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis: A Critical Moderator in the Life Cycle of Immune Cells

Abstract: Ferroptosis is a form of programmed cell death that was only recognized in 2012. Until recently, numerous researchers have turned their attention to the mechanism and function of ferroptosis. A large number of studies have shown potential links between cell ferroptosis and infection, inflammation, and tumor. At the same time, immune cells are vital players in these above-mentioned processes. To date, there is no comprehensive literature review to summarize the relationship between ferroptosis and immune cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 84 publications
1
26
0
Order By: Relevance
“…We found that patients with high ferroptosis scores experienced longer survival time. CD8 + T cells can induce ferroptosis in tumor cells, and then improve the anti-tumor effect (23). Consistently, our GSEA results showed that there was signi cant activation of immune-related pathway in ferroptosis score high group, indicating that ferroptosis may affect the prognosis through these immune pathways.…”
Section: Discussionsupporting
confidence: 81%
“…We found that patients with high ferroptosis scores experienced longer survival time. CD8 + T cells can induce ferroptosis in tumor cells, and then improve the anti-tumor effect (23). Consistently, our GSEA results showed that there was signi cant activation of immune-related pathway in ferroptosis score high group, indicating that ferroptosis may affect the prognosis through these immune pathways.…”
Section: Discussionsupporting
confidence: 81%
“…On the one hand, the ferroptosis of immune cells reduce their number and function, impairing the immune response. On the other side, the ferroptosis of non-immune cells will cause the release of damage-associated molecular pattern (DAMP) and trigger immune responses ( Wang and Lu, 2022 ). Zou et al ( Wang et al, 2019 ) found that IFN γ derived from immunotherapy-activated CD8 + T cells could down-regulate SLC3A2 and SLC7A11 levels, leading to decreased cystine uptake and enhanced tumor lipid oxidation and ferroptosis.…”
Section: The Role Of Ferroptosis In Tumorsmentioning
confidence: 99%
“…Studies have revealed that ferroptosis plays a direct role in the immune response, and that immune cells undergo ferroptosis under specific conditions, causing impaired immune activity [ 45 ]. These facts, combined with our work, lead us to believe that immune cell ferroptosis increased in Per1/Per2 DKO mice in old age (14 months), and is responsible for the decreases in immune cell numbers, affecting the spleen’s immune function in mice.…”
Section: Discussionmentioning
confidence: 99%